2008
DOI: 10.1158/1055-9965.epi-08-0025
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Carcinogenic Polycyclic Aromatic Hydrocarbons in Mate Drinks

Abstract: Background: Drinking mate has been associated with cancers of the esophagus, oropharynx, larynx, lung, kidney, and bladder. We conducted this study to determine whether drinking mate could lead to substantial exposure to polycyclic aromatic hydrocarbons (PAH), including known carcinogens, such as benzo[a]pyrene. Methods: The concentrations of 21 individual PAHs were measured in dry leaves of eight commercial brands of yerba mate and in infusions made with hot (80°C) or cold (5°C) water. Measurements were done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 28 publications
4
79
0
3
Order By: Relevance
“…In fact, the same mechanism applies to mate (Vassallo et al, 1985;Victora et al, 1987;De Stefani et al, 1990;Castelletto et al, 1994;Rolon et al, 1995;Castellsague et al, 2000;Sewram et al, 2003;De Stefani et al, 2003). It should be taken into account that mate contains benzo(a)pyrene, a ubiquitous carcinogen (Fagundes et al, 2006;Kamangar et al, 2008). In fact the role of benzo(a)pyrene in the aetiology of squamous cell oesophageal cancer has not been extensively studied to date.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, the same mechanism applies to mate (Vassallo et al, 1985;Victora et al, 1987;De Stefani et al, 1990;Castelletto et al, 1994;Rolon et al, 1995;Castellsague et al, 2000;Sewram et al, 2003;De Stefani et al, 2003). It should be taken into account that mate contains benzo(a)pyrene, a ubiquitous carcinogen (Fagundes et al, 2006;Kamangar et al, 2008). In fact the role of benzo(a)pyrene in the aetiology of squamous cell oesophageal cancer has not been extensively studied to date.…”
Section: Discussionmentioning
confidence: 94%
“…The inhabitants of this high-risk area have the common habit of drinking large amounts of hot mate (a local beverage derived from the herb called Ilex paraguariensis) (Heck et al, 2007). Although it has been postulated that the noxious effects of mate are due to the hot temperature of the beverage (IARC, 1991), recent studies conducted in Brazil by local researchers and other researchers from the National Cancer Institutes of USA have suggested that mate drinks are rich in benzo(a)pyrene, a potent carcinogen (Fagundes et al, 2006;Kamangar et al, 2008). Therefore there is room for future studies on the relationship between oesophageal carcinoma and the habit of drinking hot mate.…”
Section: Introductionmentioning
confidence: 99%
“…According to a monograph published by the International Agency for Research on Cancer (IARC), hot 'mate' drinking has been considered as a 2A agent, that is, a possible carcinogenic for humans (IARC, 1991). In fact, some studies found high levels of carcinogenic polycyclic aromatic hydrocarbons (PAH) (Gomes Zuin et al, 2005;Kamangar et al, 2008;Abnet, 2007;Golozar et al, 2012). A recent paper reported the presence of 8 PAHs in hot and cold 'mate' infusions (Thea et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Diferentes concentrações de hidrocarbonetos aromáticos policíclicos (HAP) são encontradas na erva mate nos diferentes produtos comerciais e nas preparações a quente e a frio (Zuin et al, 2005;Kamangar et al, 2008). Isto sustenta a hipótese que o risco de câncer associado com ingestão de mate pode não estar relacionado somente à temperatura, mas também ao nível de compostos carcinogênicos presentes (Loria et al, 2009).…”
Section: Introductionunclassified